2022
DOI: 10.4269/ajtmh.20-1540
|View full text |Cite|
|
Sign up to set email alerts
|

Clinico-Etiological Profile and Predictors of Mortality of Nontraumatic Coma in Children of Upper Egypt: A Prospective Observational Study

Abstract: Nontraumatic coma (NTC) is a considerable cause of morbidity and mortality in children. This prospective observational study aimed to determine the clinico-etiological profile of NTC in children and delineate clinical signs predicting mortality in Upper Egypt from June 2019 to May 2020. All children from 1 month of age to 16 years who were admitted with NTC were included in the study. All patients received full histories and physical examinations, including Glasgow Coma Scale (GCS). Routine laboratory investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
0
0
Order By: Relevance
“…This is consistent with the findings of other studies (Nijar, 2022;Schmidt et al, 2021). The mortality rate of 14.2%, as reported in our study, was lower than previous studies, which reported 25% (Baseer et al, 2022) and 34% (Biswas et al, 2021)mortality. Though the mortality rate in these studies was higher than ours, it was significantly lower than the adult mortality rate of 60% (Shafiee et al, 2022).…”
Section: Discussionsupporting
confidence: 94%
“…This is consistent with the findings of other studies (Nijar, 2022;Schmidt et al, 2021). The mortality rate of 14.2%, as reported in our study, was lower than previous studies, which reported 25% (Baseer et al, 2022) and 34% (Biswas et al, 2021)mortality. Though the mortality rate in these studies was higher than ours, it was significantly lower than the adult mortality rate of 60% (Shafiee et al, 2022).…”
Section: Discussionsupporting
confidence: 94%